Science.technology and every day life 1870-1950 - Chant, Colin (ed.) (London, 1989)
Outlines the nature of changes in key areas such as materials, communications and goods and examines the new ideologies of Taylorism and Fordism discussing questions of technological determinism. This book should be of interest to Open University course A282, students and teachers of social history.
Keywords: Science Social aspects